Is the WHO Creating Unnecessary Confusion Over Breast Milk Substitutes?. Issue 6 (December 2018) - Forsyth, Stewart
Abstract : ABSTRACT: A recent statement by WHO that "breast milk substitutes should be understood to include any milks …that are specifically marketed for feeding infants and young children up to the age of 3 years" differs significantly from the definition in the International Code which states "a breast milk substitute is any food being marketed or otherwise presented as a partial or total replacement for breast milk, whether or not suitable for that purpose." The new interpretation, which lacks consultation and endorsement, is also ambiguous, with the boundaries between breast milk substitutes and complementary foods being blurred during the first 3 years of life. The logical definitions of breast milk substitutes and complementary foods contained within the Code should be maintained and inappropriate promotion of foods and fluids for infants and young children should be addressed through effective regulation of composition and labelling standards.